Socialization of Study on Application of Water Hyacinth Extract as an Inhibitor to Prevent Corrosion: Sosialisasi Studi Penerapan Ekstrak Eceng Gondok Sebagai Inhibitor Untuk Mencegah Korosi - Novrianti; Ayyi Husbani; Yolly Adriatic; Richa Melysa; Irwan Anwar; Muhammad Iqbal (Journal of Community Service and Application of Science, 2024)
Corrosion or rusting usually occurs in metal-based equipment due to a decrease in the quality of the metal due to electrochemical reactions with the environment. Metals are widely used in life, from household appliances to health equipment. This Community Service Activity has a theme Utilization of water hyacinth extraction as a corrosion inhibitor to overcome corrosion problems. Socialization of the method or process of corrosion, the losses that occur due to corrosion and the process/method of extracting water hyacinth to become a corrosion inhibitor and its application to reduce the rate of corrosion was carried out with the youth of Muhammadiyah Kampar, Batu Belah Village because the use of water hyacinth plants is still not optimal and is even considered to disturb the environment because it can reduce water discharge. This community service can increase insight and can be applied in life to prevent corrosion that occurs on equipment used in everyday life